Long‐term opioid use in curative‐intent radiotherapy: One‐Year outcomes in head/neck cancer patients. Issue 4 (30th November 2019) - Schumacher, Leif‐Erik D.; Sargi, Zoukaa B.; Masforroll, Melissa; Kwon, Deukwoo; Zhao, Wei; Rueda‐Lara, Maria A.; Freedman, Laura M.; Elsayyad, Nagy; Samuels, Stuart E.; Abramowitz, Matthew C.; Samuels, Michael A.
Abstract: Background: No study has determined the incidence of long‐term opioid use, or risk factors for long‐term use, ≥1 year after radiotherapy. Methods: Medical records of 276 head/neck cancer patients were retrospectively assessed for persistent opioid use 1‐year after curative‐intent radiotherapy. Numerous potential risk factors were assessed and the physicians' documented reasons for continued use were qualitatively categorized as suspected opioid use disorder (OUD) or as medically indicated for control of ongoing pain. Results: Of note, 20 of 276 patients continued using opioids long‐term. High maximum opioid dose and the use of opioids and/or psychotropics/non‐opioid analgesics at the radiation oncology intake visit were associated with this outcome. Three patients continued due to suspected OUD and 17 due to medical indications. Conclusion: Of note, 7.2% of patients developed long‐term opioid use, which was associated with high maximum opioid dose and early initiation of opioids and/or psychotropics/non‐opioid analgesics. Physicians cited medical indications as the primary reason for continued use.